2018
DOI: 10.2463/mrms.mp.2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-driven Pulsatile Motion of Intracranial Cerebrospinal Fluid Visualized Based on a Correlation Mapping Technique

Abstract: Purpose:A correlation mapping technique delineating delay time and maximum correlation for characterizing pulsatile cerebrospinal fluid (CSF) propagation was proposed. After proofing its technical concept, this technique was applied to healthy volunteers and idiopathic normal pressure hydrocephalus (iNPH) patients.Methods:A time-resolved three dimensional-phase contrast (3D-PC) sampled the cardiac-driven CSF velocity at 32 temporal points per cardiac period at each spatial location using retrospective cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…One of the advantages of 4D‐PC is that this method can directly and noninvasively measure human intracranial arterial hemodynamics in individual subjects . The 4D‐PC method has also been used to quantify the spatiotemporal velocity distribution of CSF motion as vector cine images . The 4D‐PC technique can visualize the propagation of pulsatile CSF motion even in spaces separated by a thin membrane‐like structure through which no spin travels, such as the Liliequist membrane or an arachnoid cyst wall .…”
Section: Other Methods Using Mrimentioning
confidence: 99%
“…One of the advantages of 4D‐PC is that this method can directly and noninvasively measure human intracranial arterial hemodynamics in individual subjects . The 4D‐PC method has also been used to quantify the spatiotemporal velocity distribution of CSF motion as vector cine images . The 4D‐PC technique can visualize the propagation of pulsatile CSF motion even in spaces separated by a thin membrane‐like structure through which no spin travels, such as the Liliequist membrane or an arachnoid cyst wall .…”
Section: Other Methods Using Mrimentioning
confidence: 99%
“…The phase-contrast method has also been utilized to visualize fluid flow. Recently, the visualization of CSF dynamics using four-dimensional phase-contrast (4D-PC) has been developed, which determines the quantitative spatiotemporal velocity distribution of CSF motion as vector cine images ( 47 ). One study using 4D-PC reported significantly lower CSF velocity in the posterior part of the lateral ventricle around the choroid plexus than that in other regions, a finding that challenged the traditional theory that choroid plexus pulsation is the driving force of CSF flow ( 48 ).…”
Section: Imaging Evaluation Of the Glymphatic System/neurofluid Dynammentioning
confidence: 99%
“…Cardiac-gated PC velocity measurement was performed in three spatial directions at 1.5 T for 13 young, healthy volunteers (8 males and 5 females with mean AE SD age of 29 AE 5); 13 elderly, healthy volunteers (4 males and 9 females with mean AE SD age of 72 AE 8); and 13 patients with iNPH (2 males and 11 females with mean AE SD age of 75 AE 5). Detailed imaging conditions are shown elsewhere [10].…”
Section: Csf Motion Visualization Based On Cardiac-gated Pc Imagingmentioning
confidence: 99%
“…After validating the appropriateness of the correlation mapping technique in a flow phantom [10], it was applied to three subject groups. The reference region was set at CSF near the basilar artery in the midline slice to visualize CSF motion propagation derived from the cardiac pulsation [9].…”
Section: Correlation Mappingmentioning
confidence: 99%
See 1 more Smart Citation